2013
DOI: 10.7570/kjo.2013.22.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Association between Personality and Eating Style in Korean Obese Adults

Abstract: Background: Close relations have been observed between obesity and eating habits, which is affected by personality traits, however, only few studies are available and little is known concerning this topic. Methods: This study group consisted of 141 Korean participants with body mass index of at least 27 kg/m 2 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The results also showed that adolescents who skipped breakfast or ate fast foods more often were relatively likely to be vulnerable. Such findings were consistent with those of previous studies reporting that unhealthy dietary habit is highly associated with neurosis [ 28 , 29 ]. Therefore, applying specific and systematic programs for improving dietary habits should be helpful for these adolescents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results also showed that adolescents who skipped breakfast or ate fast foods more often were relatively likely to be vulnerable. Such findings were consistent with those of previous studies reporting that unhealthy dietary habit is highly associated with neurosis [ 28 , 29 ]. Therefore, applying specific and systematic programs for improving dietary habits should be helpful for these adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…Such findings were consistent with those of previous studies reporting that unhealthy dietary habit is highly associated with neurosis. 28,29 Therefore, applying specific and systematic programs for improving dietary habits should be helpful for these adolescents. Such programs should include education that emphasizes the importance of regular meals and provision of wellbalanced diet, which can be expected to contribute to improving mental health and reducing suicidality among adolescents.…”
Section: Discussionmentioning
confidence: 99%